Superresolution expansion microscopy reveals the three-dimensional organization of the Drosophila synaptonemal complex - Cahoon, Cori K. (Proc Natl Acad Sci U S A, 2017)
The synaptonemal complex (SC), a structure highly conserved from yeast to mammals, assembles between homologous chromosomes and is essential for accurate chromosome segregation at the first meiotic division. In Drosophila melanogaster, many SC components and their general positions within the complex have been dissected through a combination of genetic analyses, superresolution microscopy, and electron microscopy. Although these studies provide a 2D understanding of SC structure in Drosophila, the inability to optically resolve the minute distances between proteins in the complex has precluded its 3D characterization. A recently described technology termed expansion microscopy (ExM) uniformly increases the size of a biological sample, thereby circumventing the limits of optical resolution. By adapting the ExM protocol to render it compatible with structured illumination microscopy, we can examine the 3D organization of several known Drosophila SC components. These data provide evidence that two layers of SC are assembled. We further speculate that each SC layer may connect two nonsister chromatids, and present a 3D model of the Drosophila SC based on these findings.